Hubungan Koordinasi Mata Tangan, Kelincahan Dan Keseimbangan Terhadap Kemampuan Dribble Bolabasket - Sahabuddin (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2020)
This study aims to determine the relationship between hand eye coordination, agility, and balance with dribbling in basketball games. This research is a descriptive research. The population of this study were all male students of SMK Negeri 7 Makassar with a total sample of 40 people selected by random sampling. The data analysis technique used is the correlation analysis technique using the SPSS version 17.00 system at a significant level of 95% or 0.05. Starting from the results of data analysis, this study concludes that: (1) hand eye coordination has a significant relationship with dribbling in basketball games for students of SMK Negeri 7 Makassar, proven ro = -0,668 (P = 0,000 <a0,05); (2) agility has a significant relationship with dribble in the basketball game for students of SMK Negeri 7 Makassar, proven to be ro = 0.830 (P = 0.000 <a0.05); (3) balance has a significant relationship with dribble in basketball games for students of SMK Negeri 7 Makassar, proven ro = -0,828 (P = 0,000 <a0,05); and (4) hand eye coordination, agility, and balance have a significant relationship with dribbling in basketball games for students of SMK Negeri 7 Makassar, it is proven that Ro = 0.875 (P = 0.000 <a0.05)